The geological record of ocean acidification - Hoenisch, Baerbel; Ridgwell, Andy; Schmidt, Daniela N.; Thomas, Ellen; Gibbs, Samantha J.; Sluijs, Appy; Zeebe, Richard; Kump, Lee; Martindale, Rowan C.; Greene, Sarah E.; Kießling, Wolfgang; Ries, Justin; et al. (Science, 2012)
Ocean acidification may have severe consequences for marine ecosystems; however, assessing its future impact is difficult because laboratory experiments and field observations are limited by their reduced ecologic complexity and sample period, respectively. In contrast, the geological record contains long-term evidence for a variety of global environmental perturbations, including ocean acidification plus their associated biotic responses. We review events exhibiting evidence for elevated atmospheric CO2, global warming, and ocean acidification over the past ∼300 million years of Earth's history, some with contemporaneous extinction or evolutionary turnover among marine calcifiers. Although similarities exist, no past event perfectly parallels future projections in terms of disrupting the balance of ocean carbonate chemistry - a consequence of the unprecedented rapidity of CO 2 release currently taking place.
UnivIS-Import:2015-03-09:Pub.2012.nat.dgeo.IGM.LP.thegeo